2011
DOI: 10.1016/j.nrl.2010.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Trastornos del control de los impulsos y punding en la enfermedad de Parkinson: la necesidad de una entrevista estructurada

Abstract: Patients with PD do not spontaneously admit the presence of ICD or punding and these behaviours appear to be under-recognised in clinical practice. A screening questionnaire is needed to ensure their detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…While premature choices and jumping to conclusions are found in about 20% of the general population [21], our results suggest that subtle underlying impulsivity, only detectable by metric tasks may be even more common in the early stages of PD. Computerized tasks may be more valid than using self-filled questionnaires as people may either lack insight into their impulsivity or deliberately deny such impulsive tendencies [22]. …”
Section: Discussionmentioning
confidence: 99%
“…While premature choices and jumping to conclusions are found in about 20% of the general population [21], our results suggest that subtle underlying impulsivity, only detectable by metric tasks may be even more common in the early stages of PD. Computerized tasks may be more valid than using self-filled questionnaires as people may either lack insight into their impulsivity or deliberately deny such impulsive tendencies [22]. …”
Section: Discussionmentioning
confidence: 99%
“…The present study used rigorous direct interviews conducted by neurological specialists and found that the prevalence was 5.4% in patients with PD, which is consistent with the figures reported by previous studies. [ 3 , 7 , 24 , 25 ] In terms of the predisposing factors for the development of punding, high daily LED, young age of onset, being male, frequent rescue doses, long PD duration, presence of dyskinesia, and disease severity have been suggested as risk factors. Similarly, our data indicated that long duration of PD and PD medication, high total daily LED, and presence of dyskinesia and ICD were significant risk factors for developing punding behavior.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that a large proportion of PD-related ICBs are undiagnosed in routine clinical settings where the symptoms are not specifically looked for. Patients and their families often do not spontaneously disclose ICBs (Avila, Cardona et al 2011), probably for a number of reasons including embarrassment and lack of insight. Furthermore, patients and their families may think that these behaviours are unrelated to PD and therefore irrelevant to their treating physicians.…”
Section: Phenomenology and Epidemiology Of Icbsmentioning
confidence: 99%